2022
DOI: 10.3389/fpsyg.2022.823229
|View full text |Cite
|
Sign up to set email alerts
|

Singing and Social Identity in Young Children

Abstract: A range of studies suggest that singing activities with young children can have a beneficial impact on other aspects of their development. However, there is little research examining the relationship between young children's singing and their developing social identity. In the current study, data were captured of young children's singing and social identity as part of a larger-scale, longitudinal evaluation of the nationwide Sing Up programme in England. Participants were 720 children aged 5-8 years old. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Research on the psychosocial benefits of music participation is limited (Crooke et al, 2016), and most is correlational. Many studies report that music-making promotes positive self-perceptions, including feelings of social inclusion (Adderley et al, 2003; Bartolome, 2013; Hogan & Winner, 2019; Papageorgi et al, 2022), self-esteem (Costa-Giomi, 2004; Devroop, 2012; Kokotsaki & Hallam, 2007; Rickard et al, 2013), agency (Stolp et al, 2022), and well-being (Osborne et al, 2016). A study by Degé et al (2014) reported that academic self-concept was significantly correlated with length of time in music lessons in 12- to 14-year-olds, even after controlling for IQ score and demographic variables (to counteract self-selection effects).…”
Section: Executive Functioningmentioning
confidence: 99%
“…Research on the psychosocial benefits of music participation is limited (Crooke et al, 2016), and most is correlational. Many studies report that music-making promotes positive self-perceptions, including feelings of social inclusion (Adderley et al, 2003; Bartolome, 2013; Hogan & Winner, 2019; Papageorgi et al, 2022), self-esteem (Costa-Giomi, 2004; Devroop, 2012; Kokotsaki & Hallam, 2007; Rickard et al, 2013), agency (Stolp et al, 2022), and well-being (Osborne et al, 2016). A study by Degé et al (2014) reported that academic self-concept was significantly correlated with length of time in music lessons in 12- to 14-year-olds, even after controlling for IQ score and demographic variables (to counteract self-selection effects).…”
Section: Executive Functioningmentioning
confidence: 99%